1997
DOI: 10.1103/physrevlett.79.3026
|View full text |Cite
|
Sign up to set email alerts
|

MonometallofullereneTm@C82: Proof of an Encapsulated Divalent Tm Ion by High-Energy Spectroscopy

Abstract: Monometallofullerene Tm@C82: proof of an encapsulated divalent Tm ion by high energy spectroscopy Pichler, T.; Golden, M.S.; Knupfer, M.; Fink, J.; Kirbach, U.; Kuran, P.; Dunsch, L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 27 publications
4
50
0
1
Order By: Relevance
“…Interestingly, the bonding and formal valency of the R ions also depend on the number of encaged ions: Thus, X-ray angle-resolved near-edge spectroscopy (XANES) spectra revealed that Tm is trivalent in Tm 2 @C 82 whereas it is divalent in Tm@C 82 [3,4]. The divalent state, unexpected for this R ion, was also concluded from photoemission and high-energy spectroscopy data [5,6]. A complex behaviour was found for Sc k @C 82 (k ¼ 1; 2, 3): As Takata et al [7] reported, Sc is divalent for k ¼ 1 or 2, whereas for k ¼ 3 the whole trimer is trivalent, (Sc 3 ) 3+ .…”
Section: Introductionmentioning
confidence: 87%
“…Interestingly, the bonding and formal valency of the R ions also depend on the number of encaged ions: Thus, X-ray angle-resolved near-edge spectroscopy (XANES) spectra revealed that Tm is trivalent in Tm 2 @C 82 whereas it is divalent in Tm@C 82 [3,4]. The divalent state, unexpected for this R ion, was also concluded from photoemission and high-energy spectroscopy data [5,6]. A complex behaviour was found for Sc k @C 82 (k ¼ 1; 2, 3): As Takata et al [7] reported, Sc is divalent for k ¼ 1 or 2, whereas for k ¼ 3 the whole trimer is trivalent, (Sc 3 ) 3+ .…”
Section: Introductionmentioning
confidence: 87%
“…High energy spectroscopy has been proven to be a key tool to understand the complicated interplay between charge transfer and hybridisation in these molec-ular hybrid systems. For instance, for metallofullerenes, this allowed for the first time to observe of a purely ionic charge transfer and to unravel the stabilization of rare earth ions with unconventional valency was established in the case of Tm@C 82 [7]. On the other hand for dimetallofullerenes and trimetalnitride fullerenes such as Sc2@C 84 and Dy 3 N@C 80 the encaged metals are not purely 2+ viz.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, although most of the bulk elemental RE metals are trivalent, Tm forms divalent as well as trivalent and intermediate valence compounds. X-ray absorption and photoemission studies show that divalent Tm atoms are found not only in the gas phase [70], but also in rare gas matrices [71], endohedral fullerenes [72], and at low-coordinated surface sites of Tm films evaporated at low temperature [73]. Here, we find no significant difference in the XAS line shape of isolated adatoms compared to the ML sample, indicating that Tm atoms on W(110) have a stable 4f 12 ground state, which we attribute to the gain in cohesive energy of the 4f 12 5d 1 6s 2 configuration compared to the 4f 13 5d 0 6s 2 configuration [74] for Tm atoms adsorbed on a 5d metal [69].…”
Section: Electronic Ground Statementioning
confidence: 99%